2007
DOI: 10.1002/bit.21264
|View full text |Cite
|
Sign up to set email alerts
|

Deglycosylation of ovalbumin prohibits formation of a heat‐stable conformer

Abstract: To study the influence of the carbohydrate-moiety of ovalbumin on the formation of the heat-stable conformer S-ovalbumin, ovalbumin is deglycosylated with PNGase-F under native conditions. Although the enzymatic deglycosylation procedure resulted in a complete loss of the ability to bind to Concavalin A column-material, only in about 50% the proteins lost their complete carbohydrate moiety, as demonstrated by mass spectrometry and size exclusion chromatography. Thermal stability and conformational changes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Similar processes have been described in the context of heat shock proteins and HIF‐1α stabilization intracellularly [Trisciuoglio et al, ]. In a related fashion, other cytokines have been shown to rest in dormant states, extracellularly bound to matrix components and glycoproteins that are cleaved following trauma [de Groot et al, ; Axelsson et al, ]. In this case, the trauma of heat treatment may denature any bound components while preserving active sites on IL‐1 or other G‐CSF‐stimulating factors.…”
Section: Discussionmentioning
confidence: 79%
“…Similar processes have been described in the context of heat shock proteins and HIF‐1α stabilization intracellularly [Trisciuoglio et al, ]. In a related fashion, other cytokines have been shown to rest in dormant states, extracellularly bound to matrix components and glycoproteins that are cleaved following trauma [de Groot et al, ; Axelsson et al, ]. In this case, the trauma of heat treatment may denature any bound components while preserving active sites on IL‐1 or other G‐CSF‐stimulating factors.…”
Section: Discussionmentioning
confidence: 79%
“…Spectroscopic studies indicated that the conformational change is very limited and involves a small alteration in the secondary structure, without a major alteration in the overall folding of the protein (Huntington et al, 1995;de Groot et al, 2007). Because ovalbumin is transformed into S-ovalbumin irreversibly during prolonged storage of shelled eggs and the formation velocity is only affected by pH and temperature, it was chosen as the reference index to express the freshness of the commercial shell eggs in the equivalent age (Smith and Back, 1965;Masaaki, 2005;de Groot et al, 2007).…”
Section: Formation Kinetics Of S-ovalbuminmentioning
confidence: 99%
“…At the same time, the adsorption efficiencies of glycoproteins were much higher than those of non‐glycoproteins, and the adsorption efficiencies of Ova, IgG, γ‐Glo, and ConA increased gradually as the NaCl concentration increased. Ova has a solvent‐exposed carbohydrate chain containing four to six mannose residues and two to four N ‐acetyl‐β‐ d ‐glucosamine residues, and the surface of HRP is neutral under tested pH conditions; therefore, the hydroxyl groups of these two glycoproteins were exposed and the adsorption efficiencies were largely unaffected by the ionic strength. The sugar moiety of IgG consisting of 30 different bi‐antennary glycan structures is buried within the hydrophobic core between two constant fragments .…”
Section: Resultsmentioning
confidence: 99%